The Bond Scheduling Problem of the Multi-Subsidiary Holding Company - Baker, Kenneth R.; Vander Weide, James H. (Management Science, 1982)
This paper presents a decision-theoretic model of the bond scheduling problem faced by a multi-subsidiary holding company such as AT&T or GTE. The objective is to minimize the total cost of bond flotations across all subsidiaries, where total cost is the sum of the yield paid to investors, the flotation expense associated with the preparation of each issue and the opportunity expense to each subsidiary of not meeting its request at the desired time. Our model suggests that the timing of bond issues is primarily a problem in trading off the diseconomies of issuing many bonds in one month with the penalty costs of delay. An efficient dynamic programming algorithm for solving the problem is also presented along with an example.